2011
DOI: 10.1016/j.clay.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of a hydrophobic natural dye by intercalation into organo-montmorillonite

Abstract: 19The stability of the naturally occurring annatto dye against irradiation with visible light 20 was enhanced by intercalation into octyl trimethylammonium and dodecyl 21 trimethylammonium montmorillonite. The intercalated dye exhibited improved light fastness. 22

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
1
22
1
Order By: Relevance
“…The most prominent approach for organic and especially natural dye protection is their intercalation into inorganic clays, thus having complete operations with “green” natural materials . Abundant bulk clays have to be exfoliated for this purpose, converting to nanomaterials either of lamellar structure with alumo or magnesium/silicate sheets (like kaolin, montmorillonite, bentonite, and hydrotalcite) or tubule and fiber structures (halloysite, imogolite, sepiolite, and palygorskite) ( Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…The most prominent approach for organic and especially natural dye protection is their intercalation into inorganic clays, thus having complete operations with “green” natural materials . Abundant bulk clays have to be exfoliated for this purpose, converting to nanomaterials either of lamellar structure with alumo or magnesium/silicate sheets (like kaolin, montmorillonite, bentonite, and hydrotalcite) or tubule and fiber structures (halloysite, imogolite, sepiolite, and palygorskite) ( Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…We expected nanoclay to be a significant factor because the selected natural dyes were anionic. However, the surfactant-silane modifiers allowed adsorption in both nanoclays because of nanoclay interlayer and surface modifications [21]. Performance during the synthesis process under these conditions depended only on the molecular structure of the natural dyes, e.g.…”
Section: Adsorptionmentioning
confidence: 99%
“…Performance during the synthesis process under these conditions depended only on the molecular structure of the natural dyes, e.g. aggregation, orientations and charge density [22,21].…”
Section: Adsorptionmentioning
confidence: 99%
“…It is reported that various dyes could be stabilized by their adsorption into the interlayer of clays 7,8,12,13) or pores of MPS 3,9,10) . However, AD dyes tend to decompose more easily than AN dyes as the sugar chain from anthocyanin has been removed by hydrolysis in the former.…”
mentioning
confidence: 99%